(3EYLGR GdbQBfs
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3hGSJOQchG eG aGJ Cgd GdOjf hfHghG Ydi eG Zad Yfg aVdGA GdeSdejf s
(3BNQgG (B:s
(3eKd SdeGf GdaGQS aEfg eY RgOg cGf eYOhOkG ai GdMceGA hGdYdeGA bGd GdfHi U SdeGf efG Cgd GdHjJ Ke CHhPQ s
(3GdeNWhW dCMO YdeGA GdbQf GdQGHYs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJaSjQ hYdhe GdbQBfs